Prevention of terrorism - Coester, Marc (Tübinger Schriften und Materialien zur Kriminologie, 2007)
This report illustrates the output of the forth local seminar – the last one of a series being coordinated by the European Forum for Urban Security within the project “SecuCities – Cities against terrorism” – which was held in Tübingen from 27th to 28th November 2006. Organized by the Institute of Criminology of the University of Tübingen the conference with the topic “How to deal with Terrorist Threats? Major problems and Handling Opportunities for local Authorities”was thematically structured in three main topics: Firstly general information about terrorism was provided, which included historical and functional aspects of terrorism in order to get a topic-overview. Furthermore the problems and issues of the logistics, the acquisition of material, the financial structure as well as the techniques of recruitment of terrorist groups were worked out by means of the analysis of a certain terrorist group (PKK) and certain terrorist techniques. Having acquired the basic principles, the participants secondly turned to long-term strategies against terrorist threats. The main focuses of this part were the practical issues in the fight against terrorism, particularly the possibility and the capability of working on confident building measures in order to reach groups with a high potential of terrorist recruitment. Moreover it was amongst others stressed that a co-operation between different institutions – containing elements of psychology, sociology, criminology and Islam science – could become a solving factor in analyzing and preventing terrorism. Thirdly the plenum dealt with counter-terrorism measures from the cities´ perspective focusing on concrete measures of both urban terrorism prevention and crisis management in case of a terrorist attack. To name just a few points, safety and security measures at large events, the advantages and disadvantages of CCTV as well as possible reactions to bioterrorism were presented. Finally the plenary discussion provided the opportunity of an unresisted exchange of ideas. Within this discussion the participants agreed that – facing terrorism – an international as well as national and local co-operation of agencies and authorities are of prime importance.